The Deconstruction of Horror Film Formula in Midsommar by Ari Aster (2019) - Hapsari, Nabila; Fatmawaty, Lynda Susana Widya Ayu; Aeni, Eni Nur (Universitas PGRI Semarang, 2023)
The research entitled The Deconstruction of Horror Film Formula in Midsommar by Ari Aster aims to figure out the deconstruction of the horror film formula in Midsommar in contrast to horror film formula in general by Brigid Cherry. The researcher used a qualitative method to analyze the data. The primary data are taken from Ari Aster's movie, Midsommar, in the form of cinematic codes such as setting, lighting, sound, and color. In addition, the researcher also used deconstruction theory in literature and cultural elements such as Scandinavian culture to analyze the deconstruction of horror film formulas in Midsommar film. The researcher found four binary oppositions of the horror film formula in Midsommar. The first one is the deconstruction of setting where Midsommar changes the common horror film formula setting of terrifying into peaceful. The second one is the deconstruction of lighting as Midsommar uses bright lighting instead of the common dark one. The third one is the deconstruction of sound as Midsommar uses dramatic sound instead of the common creepy one. Lastly, the deconstruction of color in Midsommar as it uses various colors instead of monotone ones that are commonly used in the horror film. This research illustrated the deconstruction of the horror film formula in the movie Midsommar from Brigid Cherry's common original formula by reversing the non-dominant elements into becoming the dominant elements.